Rotational flow and thermal behavior of ternary hybrid nanomaterials at small and high Prandtl numbers - Sarangi, M.K.; Thatoi, D.N.; Nayak, M.K.; Prakash, J.; Ramesh, K.; Azam, M. (International communications in heat and mass transfer, 2022)
In this study, rotational flow and heat transfer characteristics of Al2O3 + SiC + MWCNT + water composite nanofluid towards a stretched surface emplaced in a Darcy-Forchheimer medium have been investigated. Energy equation is modeled by considering radiative heat flow and viscous dissipation effects. Suction mechanism and convective boundary heating are taken into consideration. Fourth order Runge-Kutta method along with shooting approach is used to produce the appropriate numerical solution. A comparison of our findings with previous research reveals a remarkable degree of concordance. For both ternary (Al2O3, SiC and MWCNT) and unary (Al2O3) nanoparticles, relevant characteristics are described on velocity, temperature, local skin friction, and Nusselt number profiles. Numerical results conveyed that prominent decelerated flow of ternary hybrid nanofluid is attained due to amplification of rotation parameter in Darcy-Forchheimer medium subject to both low Pr(Pr = 0.01) and high Pr(Pr = 10000) than unary nanofluid. Axial velocity peters out by 11.76% (at low Pr (Pr = 0.01)) and 12.5% (at high Pr (Pr = 10000)) for ternary hybrid nanofluid (THNF) while it whittles down by 21.42% (at low Pr) and 20% (high Pr) for unary nanofluid (UNF) subject to fluid (UNF/THNF) flows in Darcy medium (Fr = 0) and non-Darcy medium (Fr = 3). In addition, heat transfer rate from the rotating surface emaciates significantly by 119% for THNF at Br = 1.5, Bi = 1 from low Pr(Pr = 0.01) to high Pr(Pr = 10000). •A mathematical model has been developed to discuss the outcomes of the influence of Darcy-Forchheimer effect on rotational motion of ternary hybrid nanofluid (THNF) and unary nanofluid (UNF).•To investigate the impact of extremely low and extremely high Prandtl numbers on rotational flow and heat transfer.•Biomimetic energy systems based on Darcy-Forchheimer flow and nanotechnology can benefit from the model's outputs, which can also be used as a benchmark for more sophisticated computational multiphysics simulations and experimental studies.